ROLE OF STEROIDS IN PREVENTION OF RECURRENCE OF CHRONIC SUBDURAL HEMATOMA OPERATED CASES: A PROSPECTIVE STUDY - Dr. Jayant Jain; Dr. Oshin Chauhan; Dr. Sanjeev Attry; Dr. Nishtha Vashisth (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BackgroundChronic subdural hematoma (CSDH) represents a significant neurosurgical challenge, particularly in the elderly population. Despite surgical intervention being the primary treatment modality, recurrence rates remain concerning, ranging from 5-30%. This study investigated the efficacy of postoperative steroid administration in preventing CSDH recurrence and improving neurological outcomes.MethodsA prospective randomized controlled study was conducted between November 2023 and October 2024, involving 84 patients who underwent burr-hole surgery for CSDH. Patients were equally randomized into either the steroid group (n=42) receiving postoperative dexamethasone or the control group (n=42). The study evaluated recurrence rates, neurological outcomes using the modified Rankin Scale (mRS), radiological resolution and complications over a 6-month follow-up period.ResultsThe steroid group demonstrated significantly lower recurrence rates (7.1% vs 19.0%, p=0.04) and better neurological improvement (mean mRS improvement 1.8 ± 0.6 vs 1.4 ± 0.7, p=0.03) compared to the control group. Radiological resolution was superior in the steroid group (92.9% vs 76.2%, p=0.02) with shorter hospital stays (4.2 ± 1.8 vs 5.1 ± 2.1 days, p=0.04). While the steroid group showed a trend toward more minor complications, none reached statistical significance in severity or frequency.ConclusionPostoperative steroid administration effectively reduces CSDH recurrence rates and enhances neurological recovery following burr-hole surgery. The therapeutic benefits appear to outweigh potential risks when appropriate patient selection and monitoring protocols are followed.